Smart Money Moves: How Financial Traits and Confidence Shape Investment Decisions - Murtiningrum, Widiastuti (Asean International Journal of Business, 2025)
Purpose – This study is to determine the influence of financial literacy, financial behavior, overconfidence, risk tolerance and motivation in making decisions of novice investors, especially in generation Z in investing. Methodology/approach – Research methods with quantitative and associative approaches. Sample of 100 generation Z people with an age range of 12-26 years through a purposive sampling approach. Data was collected through the distribution of online questionnaires using google forms, analyzed using the Structural Equation Model (SEM) and the Partial Least Square (PLS) approach. Findings – It was found that financial literacy and risk tolerance did not have a significant effect, while financial behavior, overconfidence and motivation showed a significant influence in making the decision of generation Z to invest. Financial literacy, financial behavior, overconfidence, risk tolerance, and motivation simultaneously influence the decision to invest in generation Z Novelty/value – Investment decisions in the age group under 30 years or generation Z as novice investors, influenced by financial behavior, over confidence and motivation. With the ability to organize, plan, budget, check, manage, control, search and store their financial funds, as well as high overconfidence they are able to use their money both for consumption purposes and to invest in the capital market. Have sufficient knowledge about investment, which can influence investment decision-making behavior with the risks he will face, as well as motivation to make positive changes in his financial management with the aim of achieving prosperity. Keywords: Investment Decision, Financial Literacy, Financial Behavior, Overconfidence, Risk Tolerance, Motivation